2014
DOI: 10.1080/1068316x.2014.902454
|View full text |Cite
|
Sign up to set email alerts
|

The endorsement of cognitive distortions: comparing child pornography offenders and contact sex offenders

Abstract: This study examined the endorsement of cognitive distortions in child pornography offenders (CPOs), using an established assessment tool, the Abel and Becker Cognition Scale. The scale was expanded to include cognitions specific to child pornography offending, extracted from Howitt and Sheldon's Children and Sexual Activities Inventory (C&SA). Three samples of CPOs, child sex offenders and offenders with both offence types responded to the cognition items. An exploratory Principal Component Analysis suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 39 publications
2
42
1
4
Order By: Relevance
“…Results from the C&SA (Howitt & Sheldon, 2007) highlighted some potential differences in the cognitions between CSEMOs and CSOs, such as the finding that CSEMOs were more likely to endorse items relating to the implicit theory of Children as Sexual Beings. However, these findings were not confirmed in a recent study on the C&SA; Merdian et al (2014) found little support of these items amongst CSEMOs, with contact sex offenders scoring significantly higher on items relating to Justification, Children as Sexual Agents, and Power and Entitlement. In addition, both the IBAQ and the C&SA presented with poor psychometric properties, which do not allow for firm conclusions at this stage.…”
Section: The Endorsement Of Permission-giving Thoughts Amongst Csemoscontrasting
confidence: 50%
See 3 more Smart Citations
“…Results from the C&SA (Howitt & Sheldon, 2007) highlighted some potential differences in the cognitions between CSEMOs and CSOs, such as the finding that CSEMOs were more likely to endorse items relating to the implicit theory of Children as Sexual Beings. However, these findings were not confirmed in a recent study on the C&SA; Merdian et al (2014) found little support of these items amongst CSEMOs, with contact sex offenders scoring significantly higher on items relating to Justification, Children as Sexual Agents, and Power and Entitlement. In addition, both the IBAQ and the C&SA presented with poor psychometric properties, which do not allow for firm conclusions at this stage.…”
Section: The Endorsement Of Permission-giving Thoughts Amongst Csemoscontrasting
confidence: 50%
“…Using items from Howitt and Sheldon's cognitive distortion measure, Merdian et al (2014) found that CSEMOs scores were generally lower on these items than CSOs, and significantly so on items relating to Justification (e.g. "A man is justified in having sex with his children or step-children, if his wife does not like sex"), Children as Sexual Agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. überstei-gertes Selbstbewusstsein, Verzerrungen bei Opferempathie, kognitive Impulsivität) festgestellt, bei den Internetpornografietätern eher erhöhte Werte bei der Identifikation mit fiktionalen Charakteren, Selbstunsicherheit und motorischer Impulsivität (Elliott et al 2009;Bates und Metcalf 2007). Täter, die ausschließlich wegen Kinderpornografie verurteilt waren, wiesen außerdem eine signifikant geringere Wahrscheinlichkeit der Zustimmung zu typischen kognitiven Verzerrungen von Missbrauchstätern auf als Tä-ter, die auch sexuelle Übergriffe begangen haben (Merdian et al 2014). Unterschiede zwischen den beiden Gruppen wurden auch in einer Metaanalyse bestätigt, die zeigte, dass Internettäter eine höhere Opferempathie, weniger Selbstdarstellungsbedürfnis, aber eine stärker ausgeprägte sexuelle Devianz aufweisen (Seto et al 2001;Malamuth et al 2000).…”
Section: Konsummotivation Und Kognitionenunclassified